Wakhan: Concomitance of the Local and International in Marginal Boundaries. Issue 5 (19th October 2020) - Weaver, Duncan
ABSTRACT: Wakhan, northeast Afghanistan's peripheral panhandle, is situated between Afghanistan's borders with Tajikistan, China and Pakistan. Once subject of Great Game rivalry, it requires multiagency fieldwork to better understand its geopolitical vulnerabilities. Existing accounts of Wakhan are deemed inadequate and inappropriate, exceptionalising its wildness and wilderness, and drawing (in)civility distinctions that legitimise a near-divine right to dominion. Reassessing Wakhan in a boundary biography, the paper argues that by conceiving boundaries as local manifestations of international dynamics, marginal boundary regions can serve as tests for the 'state' of international affairs. The paper firstly assesses evolving understandings of boundaries before conceiving them as local manifestations of international dynamics. Existing narratives are then observed to render the region subaltern. Wakhan is thereafter rethought in a boundary biography revealing how marginal boundary regions are malleable instruments of statecraft. Wakhan is observed, in the assessment, to continuously reflect the changing 'state' of international affairs. Such reassessment rids Wakhan of its 'wild' otherness, transitioning it from untaken virgin land to a vulnerable periphery, forced to adapt to exogenous change. Rethought in this way, Wakhan constitutes a local site of international contestation, a demonstration that place at the margin has the potential to be concurrently local and international.